Analysis of Motivation, Work Environment, Competence and Discipline on Employee Performance of PDAM Tirtanadi Sunggal Branch Medan - Muhammad Arya Putra Fadlillah; Ikhah Malikhah; Soulthan Saladin Batubara (International Journal of Integrative Sciences, 2024)
The purpose of this study is to assess the impact of motivation, work environment, competence and discipline on employee performance at the PDAM Tirtanadi Sunggal Medan Branch. This study employs multiple linear regression analysis, census method, and associative methodology with a sample of 70 employees. SPSS Version 23 was used to process the data. The findings indicate that while competence and discipline have no substantial impact on employee performance, work environment and motivation do. All factors simultaneously impact employee performance, but discipline in relation to working hours remains a  concern. Motivation and the non-physical work environment play a significant part in this